2009
DOI: 10.4314/ejhd.v23i1.44836
|View full text |Cite
|
Sign up to set email alerts
|

Community awareness about malaria, its treatment and mosquito vector in rural highlands of central Ethiopia

Abstract: Background: Despite the rapid expansion of malaria into highland areas of Ethiopia and the movement of malaria inexperienced people to endemic areas, there is no enough information about how highland communities perceive malaria. Objective: To assess communities' awareness of malaria and its mosquito vector in highland rural communities of central Ethiopia. Methods: A community-based cross-sectional survey involved 770 heads of household was conducted during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
2
10
4
Order By: Relevance
“…The questionnaire survey results showed that all respondents had ever heard of malaria and more than 90% of them believed that malaria was one of the most important health problems of the community affecting both sex and all age groups, which is consistent with previous reports [24,25]. Most of the respondents were also familiar with at least one of the classical symptoms of malaria which is expected for a population in endemic areas where people are aware of the clinical manifestations of the disease [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…The questionnaire survey results showed that all respondents had ever heard of malaria and more than 90% of them believed that malaria was one of the most important health problems of the community affecting both sex and all age groups, which is consistent with previous reports [24,25]. Most of the respondents were also familiar with at least one of the classical symptoms of malaria which is expected for a population in endemic areas where people are aware of the clinical manifestations of the disease [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is higher than the study conducted in rural part of central Ethiopia (42.6%) [34]. Therefore, this level of perception among respondents in this study is encouraging to take appropriate preventive measures and proper use of mosquito nets.…”
Section: Discussioncontrasting
confidence: 68%
“…However, this finding was lower than the study conducted in Shewa (83.8%) [21]. Among mosquito breeding sites, the participants responded that stagnant water and swampy area was 34%, which was lower than the finding of central Ethiopia (36.2%) [34] and Shewa (91.6%) [21], the indication of the highest result in Shewa might be due to the used of multiple responses for each category.…”
Section: Discussioncontrasting
confidence: 56%
“…However, knowledge of respondents is not associated with delay in malaria treatment. Similar studies elsewhere also showed that that knowledge on malaria transmission was not associated with timely treatment seeking behaviour for under-five children [23,24]. Knowledge about the role of mosquitoes on the transmission of malaria was not also associated with timely and appropriate help seeking behaviour for children even though such knowledge may promote personal protective measures, especially use of bed nets [23,24].…”
Section: Discussionmentioning
confidence: 79%